Comparative evaluation of water collection methods using multicriteria decision making analysis - Mariolakos, D. (Bulletin of the Geological Society of Greece, 2007)
The necessity for the improvement and change of the way to collect water is of great need, especially nowadays that water tends to become a limited natural resource. The aim of this project is to study and evaluate an alternative water collection method, the artificial recharge, and compare it with the conventional established method of dam construction. The evaluation tool is a Multi-Criteria Decision Making Analysis. Multi-Criteria Analysis evaluates these two methods based on certain common criteria. More precisely, each method is examined multi-dimensionally, so that all aspects and possible problems of the application of these methods are studied.